PEMODELAN DINAMIKA VIRUS RUBELLA DENGAN RISIKO SINDROM RUBELLA BAWAAN - Abadi, Abadi; Artiono, Rudianto; Prawoto, Budi Priyo (PATTIMURA UNIVERSITY, 2021)
Rubella is a common cause of childhood rash and fever. It is typically a mild infection but it can be serious condition in pregnant women, as it may cause Congenital Rubella Syndrome (CRS) in the fetus. The study aimed to model and analyze it in order to get picture about the dynamics of the rubella virus transmission. The paper discussed two models of rubella transmission involving child-bearing age women and newly born infants of infected mothers. The models are SEIR-IR without seasonality and SEIR-IR with seasonality. The results from the first model showed that a pitchfork bifurcation occurred in the dynamics of the solution of the system with constant infection rate and the increase of the infection rate value do not make impact to the incidence of rubella among infants. The second model involving seasonality gave interesting dynamics where big seasonality may lead to a more complex dynamics of the solution.